Post-operative morbidity and mortality following D2 gastrectomy in a state funded tertiary care centre in South India - Jayaraman, Chandrabose Ambedkar Maravadi; Chidambaram, Kalyanasundarabharathi; Chinnusamy, Kolandasamy; Shanmugasundaram, Rajendran; Obla, Naganathbabu Lakshmanamurthy (International Surgery Journal, 2019)
Background: Radical gastrectomy with D2 lymphadenectomy is a surgery with significant post-operative morbidity. Pre-operative malnutrition portends a poor post-operative outcome following any gastrointestinal surgery in general. This study aims at finding out whether it is feasible to perform D2 lymphadenectomy in patients presenting with significant malnutrition. Methods: In this single centre study, we retrospectively analysed the post-operative morbidity and mortality data of 46 patients who underwent D2 gastrectomy for operable gastric cancer between October 2016 to April 2019. Almost all the patients who were analysed fulfilled at least one criterion for malnutrition. Results: The morbidity rate was 39.1% and the mortality rate was 6.5% which were a little high when compared to results from other Indian centres but not prohibitive, considering the nutritional status of these patients. Almost 50% of these patients were able to complete adjuvant chemotherapy. Conclusions: D2 gastrectomy can be performed in patients with poor pre-operative nutritional status. If perioperative nutritional requirements are taken care of promptly, the post-operative outcomes can be better.